Genetic variability in the glucocorticoid pathway and treatment outcomes in hospitalized patients with COVID-19: a pilot study - Štampar, Patricija; Blagus, Tanja; Goričar, Katja; Bogovič, Petra; Turel, Gabriele; Strle, Franc; Dolžan, Vita (Frontiers in Pharmacology, 2024)
Corticosteroids are widely used for the treatment of coronavirus disease (COVID)-19. Genetic polymorphisms of the glucocorticoid receptor, metabolizing enzymes, or transporters may affect treatment response to dexamethasone. This pilot study aimed to evaluate the association of the glucocorticoid pathway polymorphisms with the treatment response and short-term outcomes in patients with severe COVID-19. Our pilot study included 107 hospitalized patients with COVID-19 treated with dexamethasone and/or methylprednisolone, genotyped for 14 polymorphisms in the glucocorticoid pathway. In total, 83% of patients had severe disease, 15.1% had critical disease and only 1.9% had moderate disease. CYP3A4 rs35599367 was the major genetic determinant of COVID-19 severity as carriers of this polymorphism had higher risk of critical disease (OR = 6.538; 95% CI = 1.19-35.914: p = 0.031) and needed ICU treatment more frequently (OR = 10; 95% CI = 1.754-57.021: p = 0.01). This polymorphism was also associated with worse disease outcomes, as those patients had to switch from dexamethasone to methylprednisolone more often (OR = 6.609; 95% CI = 1.137-38.424: p = 0.036), had longer hospitalization (p = 0.022) and needed longer oxygen supplementation (p = 0.040). Carriers of NR3C1 rs6198 polymorphic allele required shorter dexamethasone treatment (p = 0.043), but had higher odds for switching therapy with methylprednisolone (OR = 2.711; 95% CI = 1.018-7.22: p = 0.046). Furthermore, rs6198 was also associated with longer duration of hospitalization (p = 0.001) and longer oxygen supplementation (p = 0.001). NR3C1 rs33388 polymorphic allele was associated with shorter hospitalization (p = 0.025) and lower odds for ICU treatment (OR = 0.144; 95% CI = 0.027-0.769: p = 0.023). GSTP1 rs1695 was associated with duration of hospitalization (p = 0.015), oxygen supplementation and (p = 0.047) dexamethasone treatment (p = 0.022). In conclusion, our pathway-based approach enabled us to identify novel candidate polymorphisms that can be used as predictive biomarkers associated with response to glucocorticoid treatment in COVID-19. This could contribute to the patient's stratification and personalized treatment approach.